Improving Students’ Speaking Skills Through Continuous Story Technique With Pictures - Razaq, Yusuf; Asyurah, Suci; Amiruddin, Amiruddin; Satriani, Satriani; Nurhidayanti, Nurhidayanti (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
Using the continuous tale technique in the classroom, this research describes the students' speaking abilities. Its goal is to obtain answers to the following study question: